Contributions of Ultrastructural Studies to the Knowledge of Filamentous Fungi Biology and Fungi-Plant Interactions - Faoro, Franco; Faccio, Antonella; Balestrini, Raffaella (Frontiers in Fungal Biology, 2022)
Since the first experiments in 1950s, transmission electron microscopy (TEM) observations of filamentous fungi have contributed extensively to understand their structure and to reveal the mechanisms of apical growth. Additionally, also in combination with the use of affinity techniques (such as the gold complexes), several aspects of plant-fungal interactions were elucidated. Nowadays, after the huge of information obtained from -omics techniques, TEM studies and ultrastructural observations offer the possibility to support these data, considering that the full comprehension of the mechanisms at the basis of fungal morphogenesis and the interaction with other organisms is closely related to a detailed knowledge of the structural features. Here, the contribution of these approaches on fungal biology are illustrated, focusing both on hyphae cell ultrastructure and infection structures of pathogenic and mycorrhizal fungi. Moreover, a concise appendix of methods conventionally used for the study of fungal ultrastructure is provided.